Perancangan Convention dan Exhibition di Kota Bandung dengan konsep Analogi - Dwika Rifa Persada; Karya Subagya; Sri Kurniasih (MAESTRO, 2020)
Currently, Indonesia has the potential to become a commercial business area, especially in the fields of Convention and Exhibition, with the presence of a Convention and Exhiition in Bandung, it is hoped that it can increase the tourist attraction of the city. The concept of analogy is applied in the design of the Convention and Exhibition in the city of Bandung, whtch analogizes the shape of the Totopong or Sundanese headband which is an icon of the building located in the West Java region. Arifin Soedjayana as Head of the West Java Province Industry and Trade Agency, emphasized that seriousness of West Java Province in developing the meeting, incentive, convention, and exhibition (MICE), industry because this exhibition center has the potential to be well integrated with various means of transportation which is in the city of Bandung.